Expression vs. function of ABC transporters at the blood-brain barrier - Scherrmann, Jean-Michel (Henry Stewart Talks, 2019)
Introduction to the ABC superfamily and the blood-brain barrier (BBB), ABCB and P-glycoprotein (ABCB1) at the BBB, ABCG and BCRP (ABCG2) at the BBB, ABCC and the Multi-Drug Resistance Proteins (MRPs) at the BBB, ABC in isolated human brain microvessels, Pre-clinical and clinical impact in central nervous system research and drug development